Description of Basiria khouzestanensis n. sp. (Nematoda: Tylenchidae) from Iran and its phylogenetic relationships with other species in the family - Eisvand, Payam; Nejad, Reza Farrokhi; Azimi, Sedighe (Zootaxa, 2019)
Basiria khouzestanensis n. sp., recovered from the rhizosphere of orange in Khouzestan Province, south-western Iran, is described and illustrated based on morphological, morphometric and molecular data. The new species is characterized by having short body length (430–635 µm), lateral fields composed of four incisures, with non areolated bands, cephalic region smooth and continuous with body contour, stylet 9–12.5 µm long, basal bulb short and pyriform to slightly cylindrical, V = 63.3 (58–65.5), spermatheca non-offset, tail elongate-conoid, tail tip with various shapes and males with 16.5 (15–18) μm long spicules. Morphologically, the new species is similar to five known species of the genus: B. babhi, B. brevia, B. graminophila, B. lauta and B. shahidi. Morphological comparisons with these species are discussed. The sequence of the D2–D3 expansion segments of 28S rDNA gene for the new species was also used for molecular phylogenetic analysis. The phylogenetic relationships of the new species in relation to representatives of the family Tylenchidae, obtained from Bayesian inference (BI) analysis of the D2–D3 sequences, are presented and discussed. The new species clusters in a subclade containing three unidentiﬁed species of the genus Basiria from Iran with high support.